Nanotechnology, Nanomedicine, and the Kidney - Peter V. Hauser; Hsiao-Min Chang; Norimoto Yanagawa; Morgan Hamon (Applied Sciences, 2021)
The kidneys are vital organs performing several essential functions. Their primary function is the filtration of blood and the removal of metabolic waste products as well as fluid homeostasis. Renal filtration is the main pathway for drug removal, highlighting the importance of this organ to the growing field of nanomedicine. The kidneys (i) have a key role in the transport and clearance of nanoparticles (NPs), (ii) are exposed to potential NPs’ toxicity, and (iii) are the targets of diseases that nanomedicine can study, detect, and treat. In this review, we aim to summarize the latest research on kidney-nanoparticle interaction. We first give a brief overview of the kidney’s anatomy and renal filtration, describe how nanoparticle characteristics influence their renal clearance, and the approaches taken to image and treat the kidney, including drug delivery and tissue engineering. Finally, we discuss the future and some of the challenges faced by nanomedicine.